(untitled) (Modern education and development, 2025)
This article examines the representation and classification of literary conflicts within thesaurus dictionaries, with a particular focus on their semantic structure, conceptual categorization, and practical application in literary studies. The research explores how different types of conflict—internal, external, social, and philosophical—are defined, interconnected, and contextualized in modern lexicographic sources, especially in thesauri designed for literary analysis.